2020
DOI: 10.3390/w12010176
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Ampicillin Using PLA/TiO2 Hybrid Nanofibers Coated on Different Types of Fiberglass

Abstract: New photocatalytic membranes based on polylactic acid (PLA)/TiO2 hybrid nanofibers deposited on fiberglass supports were prepared and tested for the removal of ampicillin from aqueous solutions. The electrospinning technique was used to obtain hybrid nanofibers that were deposited on three types of fiberglass with different structures, resulting in three distinct photocatalytic membranes namely fiberglass fabric plain woven-type membrane, fiberglass mat-type membrane, and fiberglass fabric one-fold edge-type m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 33 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…In our study, however, the results illustrate that the IWI technique provides better results than the US method. This statement is in line with other references indicating the better efficiency when IWI was used for TiO 2 doping with the aim of obtaining active solids for the photocatalytic degradation of different organic pollutants [54][55][56][57].…”
Section: Effect Of the Methods Used For Catalyst Synthesis On Its Photsupporting
confidence: 92%
“…In our study, however, the results illustrate that the IWI technique provides better results than the US method. This statement is in line with other references indicating the better efficiency when IWI was used for TiO 2 doping with the aim of obtaining active solids for the photocatalytic degradation of different organic pollutants [54][55][56][57].…”
Section: Effect Of the Methods Used For Catalyst Synthesis On Its Photsupporting
confidence: 92%
“…The pH is chosen according to the contaminant, and it can range between acidic and basic values. Some compounds can be degraded effectively in acidic environment, near to neutral pH, or in basic pH [16][17][18]. The effect of temperature can also be a significant factor in the removal efficiency of pollutants.…”
Section: Biodegradable Polymers Combined With Tio 2 For Enhanced Photocatalytic Activitymentioning
confidence: 99%
“…By employing the electrospinning method, PLA was also applied as a polymeric nanofiber matrix for the immobilization of TiO 2 particles. In a relative study, PLA/TiO 2 hybrid fibers were prepared on fiberglass substrates, while the photocatalytic efficiency of the obtained material was tried against ampicillin [17]. For the better adherence of the nanofibers onto the used supports, the surface of the latter was covered with PLA before utilizing the electrospinning process.…”
Section: Photocatalytic Performancementioning
confidence: 99%
“…Pseudo-first order kinetic model was commonly used in number of studies to investigate 358 the antibiotic degradation process under the diferent conditions (Zhigang, Wang et al 2018, 359 Cizmic, Ljubas et al 2019, Bobirică, Bobirică et al 2020, photocatalytic degradation of sulfamethazine in aqueous solution using ZnO was reported. The findings showed that 78 and 95% of sulfamethazine were degraded after 60 min irradiation, the rate constant k obtained 2.58×10 −2 and 4.95×10 −2 min −1 without and with ZnO, respectively.…”
Section: Table 3 Kinetics Calculations: Reaction Rate Constant and Regression Coefficientsmentioning
confidence: 99%